Acceptability of text messages and knowledge change for cervical cancer screening: a Tanzanian mixed methods study. Issue 9 (19th September 2022) - Løkke, Kristian Foldager; Rasch, Vibeke; Mwaiselage, Julius; Gammeltoft, Tine; Linde, Ditte Søndergaard
Abstract : Objectives: To investigate the acceptability of a text message intervention and evaluate if text messages could increase knowledge of cervical cancer and screening. Design: This study was a substudy of a randomised controlled trial that used a mixed methods research design combining a quantitative questionnaire dataset and qualitative interview data. A before and after assessment was made of questionnaire responses. Acceptability was measured on a 6-point Likert scale and knowledge was measured through 16 binary true/false knowledge questions concerning cervical cancer and screening. Qualitative data were coded using a combined inductive–deductive approach. Setting: Ocean Road Cancer Institute in Dar es Salaam as well as Kilimanjaro Christian Medical Center and Mawenzi Regional hospital in the Kilimanjaro Region in Tanzania. Participants: Human papillomavirus (HPV) positive women who had been randomised to the intervention group and received educative and reminder messages. Qualitative interviews were conducted with a subgroup of women in the intervention group. Interventions: 15 one-way educative and reminder text messages. Results: A total of 115 women in the intervention group responded to both the baseline and follow-up questionnaire. Overall, women found it highly acceptable to receive text messages, and there was a trend towards acceptability rising between baseline and follow-up (mean: 0.22; 95% CI 0.00 to 0.44; p=0.05; t-statics=1.96). A significant increase in acceptability was found among the lowest educated and those who had not previously been screened. The qualitative interviews showed that the underlying reasons for the high acceptability rate were that the women felt someone cared for them and that the text messages were for their own benefits. The text messages did not improve the women's knowledge on cervical cancer and screening. Conclusions: Educative and reminder text messages are highly acceptable among HPV-positive Tanzanian women; however, they do not increase the women's knowledge of cervical cancer and screening. Trial registration number: clingov (NCT02509702 ).